Long term results of double plate appliance and facemask combination in the treatment of Class III malocclusion: cephalometric analysis - Emine Kaygisiz; Erdal Bozkaya; Tuba Tortop; Derviş Emre Ercan; Sema Yüksel (Gazi University, 2018)
Objective: The aim of this study was to evaluate the long term results of double plate appliance and facemask combination (DPA-FM) in treating Class III malocclusions when growth potential of the patients was close to cease or ceased. Materials and Method: The material consisted of the pretreatment (T1), posttreatment (T2), and long term (T3) lateral cephalometric and the hand-wrist radiographs of 13 patients (5 females, 8 males; mean chronological age: 11.1±1.40 years) with skeletal and dental Class III malocclusion treated with DPA-FM combination. The mean DPA-FM treatment time was 10.8±1.88 months. The hand-wrist growth and developmental stages were MP3u or Ru at T3. The mean follow-up period was 5.0±1.98 years. Friedman's Two-Way ANOVA and Wilcoxon signed-rank tests were used to evaluate the treatment (T2-T1), follow-up (T3-T2) and overall (T3-T1) results. Results: With the DPA-FM therapy, SNA and ANB angles increased (p<0.001); however, no significant differences were found in these parameters during T3-T2 period [p=0.655 (SNA), p=0.805 (ANB)]. Significant increases were found in N┴FH-A distance during the treatment (p<0.01) and follow-up (p<0.05) periods. Molar relation showed significant increases with DPA-FM in both the treatment and overall period (p<0.001). Overjet increased significantly during the treatment (p<0.001), follow-up (p<0.05), and overall (p<0.001) periods. Significant protrusion of upper incisors (U1/NA) was observed during the treatment, follow-up, and overall periods (p<0.05). U6/PP and L6/MP angles did not change during the DPA-FM treatment; however, these parameters decreased significantly during the follow-up and overall periods (p<0.05). Conclusion: In the treatment of Class III malocclusion, the DPA-FM appliance was effective. The skeletal and dental sagittal changes achieved by orthopedic treatment were maintained in the long term.